Comparison of Clinical Response to D-Mannose with Behavioral Modifications Versus Behavioral Modifications Alone in Asymptomatic Pyuria During Pregnancy: Comparison of D-Mannose with Behavioral Modifications - Balqees, Iqra; Shakir, Shadab; Dilpazeer, Sidra; Zulfiqar, Sadaf; Anjum, Zartashia; Balqees, Bushra (Pakistan Journal of Health Sciences, 2024)
The physiological and structural changes during pregnancy cause ureteral dilatation and urine stasis, which can lead to asymptomatic and symptomatic infections. Objective: To compare the clinical response between d-mannose with behavioral modifications versus behavioral modifications alone in asymptomatic pyuria during pregnancy. Methods: A quasi experimental study was conducted from April to September 2021, in the Department of Gynecology and Obstetrics Maternal and Child Health Center unit-1, PIMS, Islamabad. A total of 130 women with diagnoses of asymptomatic pyuria matching the inclusion criteria were recruited during study period and assigned to two groups by consecutive non-probability sampling method. Patients with urinary tract abnormalities, GDM, and antibiotic-treated symptomatic UTIs were excluded. Group A was instructed to take 1 g of D-mannose twice daily and follow the advises about behavioral changes.The group B was instrcucted to follow behavioral change only. pus cells in urine R.E.reports were used to evaluate response of treatments. Results: According to the study, the mean age of patients in group A was 27.69 ± 4.04 years, whereas group B had a mean age of 28.85 ± 4.12 years. The majority of patients (61.54%) were aged 15-30. Patients in group A had a mean gestational age of 23.72 ± 3.19 weeks, whereas group B had 24.26 ± 3.23 weeks. Patients had a mean BMI of 29.65 ± 3.55 kg/m2. In group A; 23 (35.18%) and in group B 11 (16.92%) cases of asymptomatic pyuria achieved reolution.Conclusions: This study found that D-mannose with behavioral adjustments resolves asymptomatic pyuria during pregnancy better than behavioral modifications alone.